Effects of arbuscular mycorrhizal inoculation on osmoregulation and antioxidant responses of blueberry plants - Tu, Jia-Le; Liu, Xiao-Min; Xiao, Jia-Xin (Bangladesh Journal of Botany, 2019)
Effects of the arbuscular mycorrhizal (AM) fungi, Glomus mosseae, G. intraradices, and G. etunicatum, on plant growth, antioxidant content, osmoregulation, and nutrition were investigated in ‘Premier’ blueberry (Vaccinium ashei) plants exposed to low-temperature stress. Low temperature decreased mycorrhizal colonization, growth, levels of leaf soluble sugar, ascorbic acid (ASA) and root viability. However, at low temperatures, levels of leaf superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) were found to increase, accompanied by increases in levels of ASA, malondialdehyde (MDA), and proline. G. mosseae especially, significantly increased levels of SOD, POD, CAT and ASA, but decreased levels of MDA in plants. AM-inoculated plants had higher contents of proline, soluble sugar, phosphorus, potassium, calcium and magnesium than non-AM-inoculated plants, especially in the G. mosseae-inoculated plants. These results indicate that G. mosseae has the potential to enhance resistance of ‘Premier’ blueberry plants against low-temperature stress through improving antioxidant content, osmotic adjustment and mineral nutrition.